Die zweite Wirklichkeit Studien zum Roman des achtzehnten Jahrhunderts - Kurth, Lieselotte E. (UNC Studies in the Germanic Languages and Literatures, 1969)
For eighteenth century readers, the contents of a novel were often perceived as part of reality. The first part of this study on the results of this view of literature is concerned both with the relevant German, French, and English criticism of the novel and the use of literature as a frame of reference in the poetry, drama, and prose writings of the day. The second part analyzes seven novels (among them Goethe's "Werther" and "Meister") whose heroes were profoundly influenced by literature. The final section sketches the continuous presence of related themes, motifs, and narrative techniques in later novels with particular emphasis on Mann's "Zauberberg".